A Ti loaded on microbial cells 3+ Doped makinoite material and its preparation and application

By doping Ti3+ ions on the surface of the makinomine, Ti3+ doped makinomine materials loaded on cells were prepared, which solved the problems of high overpotential, low selectivity and weak oxidation resistance of existing nitrogen reduction electrocatalysts, and achieved efficient and highly selective nitrogen reduction catalytic effect.

CN116024137BActive Publication Date: 2025-03-18CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310030400.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-10
Publication Date
2025-03-18
Estimated Expiration
2043-01-10

AI Technical Summary

Technical Problem

The high overpotential, low selectivity and weak oxidation resistance of existing nitrogen reduction electrocatalysts limit their application in industry.

Method used

By biosynthetic-segmented feeding method, Ti3+ doped makinomine material loaded on cells was prepared by adding Ti3+ ions at a specific time using Chivar CN32.

Benefits of technology

It improves the yield of ammonia, has high catalytic efficiency, selectivity and antioxidant properties, has stable structure, good circulation and high sustainability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116024137B_ABST
    Figure CN116024137B_ABST
Patent Text Reader

Abstract

The invention discloses a Ti loaded on microbial cells 3+ Doped makinoite material and its preparation and application. The present invention designs a biosynthesis-staged feeding method, using Shewanella CN32, adding Ti at a specific time 3+ ions, Ti on the FeS surface 3+ Ion doping. By regulating the pH of the doping reaction process, controlling the bacterial inoculation concentration and metal ion concentration, a Ti-loaded cell was prepared. 3+ Doped makinoite material. The present invention effectively improves the ability of biosynthesized makinoite (FeS) nanomaterials loaded on cells to electrocatalyze nitrogen reduction, and improves the stability and oxidation resistance of the catalytic material FeS; the present invention proposes for the first time to dope Ti in the process of biosynthetic materials. 3+ The ideas and technical methods have high promotion and application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalytic nitrogen reduction catalysts, and specifically relates to a Ti catalyst for electrocatalytic nitrogen reduction synthesized by a biological method loaded on cells. 3+ Doped makinoite catalytic material and its preparation and application. Background Art

[0002] Ammonia (NH3) is an important fertilizer, green fuel and clean energy carrier, playing a key role in the development of human society. However, the nitrogen-nitrogen triple bond has an extremely high bond energy, which makes the production process of NH3 very difficult. At present, the most commonly used method for synthesizing NH3 in industry is based on the Haber–Bosch process, which uses metal catalysts such as Fe or Ru through the reaction of N2 with H2 at high temperature (about 700K) and high pressure (about 100bar). However, this reaction is energy-intensive (accounting for 1% of the global annual supply) and has high CO2 emissions (accounting for 1.6% of global CO2 production). In recent years, electrocatalytic methods have attracted much attention due to their low energy consumption and environmentally friendly characteristics. Various types of catalysts have been developed for the electrocatalytic reduction of nitrogen to ammonia. However, the disadvantages of existing nitrogen reduction electrocatalysts such as high overpotential, low selectivity and weak oxidation resistance limit their application in industry. Therefore, it is of great significance to explore cost-effective and green N2 reduction electrocatalysts to support the growing energy demand.

[0003] Magnolia ore (FeS), whose Fe-S on the 011 surface is highly similar to the FeMoco structure on nitrogenase, is a potential excellent N2 reduction catalyst material. Doping specific atoms onto the surface of the material can improve the surface activity and electron transfer efficiency. Therefore, atomic doping of the FeS surface will likely increase the yield of ammonia. In addition, nanomaterials synthesized under microbial mediation can have higher catalytic efficiency.

[0004] In view of this, the present invention designs a biosynthesis-stage feeding method, using Shewanella CN32, adding Ti at a specific time 3+ ions, Ti on the FeS surface 3+ Ion doping. By regulating the pH of the doping reaction process, controlling the bacterial inoculation concentration and metal ion concentration, a Ti-loaded cell was prepared. 3+ Doped with makinoite material. Summary of the invention

[0005] The purpose of the present invention is to provide a Ti loaded on microbial cells 3+Doped makinoite nanomaterials and their preparation methods and applications. In the field of electrocatalytic nitrogen reduction technology, the preparation and use of this material is reported for the first time, and it has a high catalytic efficiency for the reaction of converting N2 into NH3.

[0006] A Ti loaded on microbial cells 3+ The doped makino mineral material. The microorganisms include Shewanella.

[0007] A Ti loaded on microbial cells 3+ The preparation method of the doped makino ore material comprises the following steps:

[0008] (1) adding ferric citrate and lactic acid to an anaerobic bottle containing a culture medium, heating, adding a soluble sulfur source and Bio-Tris (bis(2-hydroxyethyl)iminotris(hydroxymethyl)methane), and adjusting the pH of the solution to 7.0-9.0; the soluble sulfur source includes at least one of sodium thiosulfate and sulfite;

[0009] (2) introducing protective gas, sterilizing, cooling, inoculating Shewanella, and culturing on a shaking table;

[0010] (3) After the shaking culture, the culture medium solution turns pure black. Under anaerobic conditions, a titanium source is added to the culture medium, and the pH is adjusted to 7.0-8.5, and the culture is continued in the shaking culture medium;

[0011] (4) Under anaerobic conditions, the black precipitate is separated from the solid and liquid and collected, washed with oxygen-free water, and freeze-dried to obtain the product.

[0012] The method, step (1) is specifically: adding ferric citrate and lactic acid to an anaerobic bottle containing LB culture medium, heating at 90-100°C, adding sodium thiosulfate and Bio-Tris after the ferric citrate is completely dissolved, and using sodium hydroxide or ammonia water to adjust the solution pH to 7.0-9.0.

[0013] The method described, step (1) is specifically: the mass ratio of ferric citrate: lactic acid = (3.5-4): 1, the mass ratio of ferric citrate: sodium thiosulfate = (1-2): 1, the mass ratio of ferric citrate: Bio-Tris = (1.5-2.5): 1; the solid-liquid ratio of ferric citrate to culture medium: (4-5) g: 250 mL.

[0014] The method, step (2) specifically comprises: introducing argon gas for at least 20 minutes, sterilizing at 121°C, 101K Pa for 20 minutes; after sterilization, waiting for the culture medium to cool, shaking it well, and inoculating Shewanella with an inoculum size of 10 6 -10 10 / ml; put the anaerobic bottle in a shaker and culture at 28-32℃ and 150-200r / min.

[0015] The method, step (3) is specifically: after 10-24 hours of shaking culture, the culture medium solution turns pure black. At this time, in the anaerobic chamber, titanium trichloride aqueous solution is added to the culture medium, and sodium hydroxide is used to adjust the pH to 7.0-8.5, and the culture medium is placed in a shaking culture medium for continued culture for 6-10 days.

[0016] The method, step (4) is specifically: collecting the black precipitate in the bottle by centrifugation under anaerobic conditions, washing with oxygen-free water for at least three times, and freeze-drying at -80°C for 10-30 hours to obtain the product.

[0017] In the method described, the mass ratio used in step (3) is Ti / Fe=0.5% to 5%, and the optimal ratio is 1%.

[0018] The iron source used in the above method is ferric citrate, which will not generate precipitation in a weakly alkaline solution and is beneficial to cell utilization; the sulfur source is a soluble high-valent sulfur compound (such as sulfite) other than sulfuric acid.

[0019] The time for adding titanium trichloride aqueous solution in the above method is between 10 and 24 hours of inoculation. 3+ Completely reduced to Fe 2+ The sulfur source has just been used and FeS precipitation has not yet been generated; premature addition will lead to Ti 3+ Fe 3+ Oxidation to Ti 4+ If it is added too late, some FeS precipitation will have already occurred, which will lead to uneven doping.

[0020] The Ti loaded on the cell membrane of the present invention 3+ Application of doped makinoite nanomaterials as electrocatalytic electrode materials for electrochemical reduction of nitrogen.

[0021] The present invention also provides the Ti loaded on the cell 3+ Application of doped makinoite material as electrocatalytic electrode material for electrochemical reduction of nitrogen.

[0022] Specifically, the application method is: the Ti loaded on the microbial cells 3+ The doped makino ore material is uniformly dispersed in a mixture of oxygen-free water, oxygen-free ethanol and Nafion resin under anaerobic conditions to obtain an electrocatalytic material, and the electrocatalytic material is coated on a carbon cloth and naturally air-dried to obtain the electrode material, which is a cathode.

[0023] Further, the Ti loaded on the microbial cells is taken 3+10 mg of nanopowder of doped makinoite material was uniformly dispersed in a mixture of 475 μl of water, 475 μl of ethanol and 50 μl of Nafion resin to prepare an electrocatalytic material, and then 20 μl was coated on a 1 cm × 1 cm carbon cloth. After natural air drying, the electrochemical catalytic reduction of N2 to NH3 was tested.

[0024] The advantages of the present invention are as follows:

[0025] Only by following the steps and conditions of the present invention can Ti loaded on cells be synthesized. 3+ The new catalytic material doped with makino ore material, in the existing literature, the method of doping using chemical synthesis method cannot load the obtained nanomaterial on cells; and there is no literature report on doping using biological synthesis method. And only according to the feeding steps of the present invention, can Ti 3+ Doped Makino ore material, otherwise, Ti 3+ It is easily oxidized to Ti 4+ , which will lead to a decrease in catalytic efficiency. In terms of synthesis technology, the synthesis conditions and methods of the present invention are simple, the operation is simple, and it is easy to control; in terms of catalytic effect, the obtained catalytic material has multiple effective N2 activation sites, has high catalytic efficiency for N2 conversion to NH3, has high selectivity for N2 adsorption and fixation, has high antioxidant properties, has high structural stability, good cyclicity, high sustainability, and can continuously produce ammonia. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagrams of the molecular structure of FeS-x%Ti prepared in the present invention from top view and side view;

[0027] Figure 2 The X-ray powder diffraction (XRD) patterns of FeS-x%Ti nanocatalytic materials prepared in various embodiments and comparative examples of the present invention;

[0028] Figure 3 The scanning electron microscope image and EDS comparison image of the nanocatalytic material prepared in Example 2 of the present invention and Comparative Example 1;

[0029] Figure 3 a, b are undoped cell membrane-FeS nanomaterials. Figure 3 c, d are cell membrane-FeS-1% Ti nanocatalytic materials;

[0030] Figure 4 Linear voltammetry (LSV) spectra of nanocatalytic materials prepared in various embodiments and comparative examples of the present invention;

[0031] Figure 5The XPS full spectrum and fine spectrum of the cell membrane-FeS-x%Ti nanocatalytic material prepared in Example 2 of the present invention and Comparative Example 1;

[0032] Figure 6 The electrocatalytic nitrogen reduction performance and Faraday effect spectrum of the cell membrane-FeS-x%Ti nanocatalytic material prepared in Example 2 of the present invention;

[0033] Figure 7 This is the result of the continuous catalytic reaction of the cell membrane-FeS-x%Ti nanocatalytic material prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0034] The complete steps of the present invention are described below by means of specific examples. It should be understood that the protection scope of the present invention is not limited by the specific examples.

[0035] Unless otherwise specified, the terms used in the present invention have the meanings commonly understood by ordinary people in the art.

[0036] In the following embodiments, various methods and processes not described in detail are conventional methods in the art.

[0037] Example 1

[0038] (1) Add 4.2 g of ferric citrate and 0.93 mL of lactic acid to an anaerobic bottle containing 250 mL of LB medium, heat at 90°C for 20 min, and after the ferric citrate is completely dissolved, add 2.45 g of sodium thiosulfate and 2.1 g of Bio-Tris, and use sodium hydroxide to adjust the solution pH to 7.0;

[0039] (2) After passing argon for 20 min, sterilize at 121°C, 101 K Pa for 20 min. After sterilization, wait for the culture medium to cool, shake well, and inoculate Shewanella CN32 (purchased from Guangdong Microbial Culture Collection Center) with an inoculum size of 10 7 The anaerobic bottle was placed in a shaker and cultured at 30°C and 180 r / min.

[0040] (3) After 24 hours of shaking culture, the culture medium solution turned pure black. At this time, titanium trichloride aqueous solution (Ti / Fe=0.5%, wt) was added to the culture medium in the anaerobic chamber using a syringe, and the pH was adjusted using sodium hydroxide to keep the pH constant. The culture medium was placed in a shaking incubator and continued to be cultured for 8 days.

[0041] (4) The black precipitate in the bottle was collected by centrifugation under anaerobic conditions, washed at least three times with oxygen-free water, and freeze-dried at -80°C for 30 hours to obtain a nanomaterial of FeS-x%Ti, x=0.5.

[0042] (5) Take 10 mg of the FeS-0.5% Ti nanopowder prepared in (4) and evenly disperse it in a mixture of 475 μl of oxygen-free water, 475 μl of oxygen-free ethanol and 50 μl of Nafion resin to prepare an electrocatalytic material. Then, take 20 μl and apply it on a 1 cm×1 cm carbon cloth. After natural air drying under anaerobic conditions, the electrochemical catalytic reduction of N2 to NH3 is tested.

[0043] Example 2

[0044] (1) Add 4.2 g of ferric citrate and 0.93 mL of lactic acid to an anaerobic bottle containing 250 mL of LB medium, heat at 90°C for 20 min, and after the ferric citrate is completely dissolved, add 2.45 g of sodium thiosulfate and 2.1 g of Bio-Tris, and use sodium hydroxide to adjust the solution pH to 8.0;

[0045] (2) After passing argon for 20 min, sterilize at 121°C, 101 K Pa for 20 min. After sterilization, wait for the culture medium to cool, shake well, and inoculate Shewanella CN32 with an inoculum size of 5 × 10 8 The anaerobic bottle was placed in a shaker and cultured at 30°C and 180 r / min.

[0046] (3) After 18 hours of shaking culture, the culture medium solution turned pure black. At this time, titanium trichloride aqueous solution (Ti / Fe=1%, wt) was added to the culture medium in the anaerobic chamber using a syringe, and the pH was adjusted using sodium hydroxide to keep the pH constant. The culture medium was placed in a shaking incubator and continued to be cultured for 7 days.

[0047] (4) The black precipitate in the bottle was collected by centrifugation under anaerobic conditions, washed at least three times with oxygen-free water, and freeze-dried at -80°C for 20 h to obtain FeS-x%Ti, x=1 nanomaterials.

[0048] (5) Take 10 mg of the FeS-1% Ti nanopowder prepared in (4) and evenly disperse it in a mixture of 475 μl of oxygen-free water, 475 μl of oxygen-free ethanol and 50 μl of Nafion resin to prepare an electrocatalytic material. Then, take 20 μl and apply it on a 1 cm×1 cm carbon cloth. After natural air drying under anaerobic conditions, the electrochemical catalytic reduction of N2 to NH3 is tested.

[0049] Example 3

[0050] (1) Add 4.2 g of ferric citrate and 0.93 mL of lactic acid to an anaerobic bottle containing 250 mL of LB medium, heat at 90°C for 20 min, and after the ferric citrate is completely dissolved, add 2.45 g of sodium thiosulfate and 2.1 g of Bio-Tris, and use sodium hydroxide to adjust the solution pH to 8.0;

[0051] (2) After passing argon for 20 minutes, sterilize at 121°C, 101K Pa for 20 minutes; after sterilization, wait for the culture medium to cool, shake it well, and inoculate Shewanella CN32 with an inoculum size of 10 9 The anaerobic bottle was placed in a shaker and cultured at 30°C and 180 r / min.

[0052] (3) After 15 hours of shaking culture, the culture medium solution turned pure black. At this time, titanium trichloride aqueous solution (Ti / Fe=2%, wt) was added to the culture medium in the anaerobic chamber using a syringe, and the pH was adjusted using sodium hydroxide to keep the pH constant. The culture medium was placed in a shaking incubator and continued to be cultured for 6 days.

[0053] (4) The black precipitate in the bottle was collected by centrifugation under anaerobic conditions, washed at least three times with oxygen-free water, and freeze-dried at -80°C for 20 h to obtain FeS-x%Ti, x=2 nanomaterials.

[0054] (5) Take 10 mg of the FeS-2% Ti nanopowder prepared in (4) and evenly disperse it in a mixture of 475 μl of oxygen-free water, 475 μl of oxygen-free ethanol and 50 μl of Nafion resin to prepare an electrocatalytic material. Then, take 20 μl and apply it on a 1 cm×1 cm carbon cloth. After natural air drying under anaerobic conditions, the electrochemical catalytic reduction of N2 to NH3 is tested.

[0055] Example 4

[0056] (1) Add 4.2 g of ferric citrate and 0.93 mL of lactic acid to an anaerobic bottle containing 250 mL of LB medium, heat at 90°C for 20 min, and after the ferric citrate is completely dissolved, add 2.45 g of sodium thiosulfate and 2.1 g of Bio-Tris, and use sodium hydroxide to adjust the solution pH to 9.0;

[0057] (2) After passing argon for 20 minutes, sterilize at 121°C, 101K Pa for 20 minutes; after sterilization, wait for the culture medium to cool, shake it well, and inoculate Shewanella CN32 with an inoculum size of 10 10 The anaerobic bottle was placed in a shaker and cultured at 30°C and 180 r / min.

[0058] (3) After 15 hours of shaking culture, the culture medium solution turned pure black. At this time, titanium trichloride aqueous solution (Ti / Fe=5%, wt) was added to the culture medium in the anaerobic chamber using a syringe, and the pH was adjusted using sodium hydroxide to keep the pH constant. The culture medium was placed in a shaking incubator and continued to be cultured for 6 days.

[0059] (4) The black precipitate in the bottle was collected by centrifugation under anaerobic conditions, washed at least three times with oxygen-free water, and freeze-dried at -80°C for 20 h to obtain FeS-x%Ti, x=5 nanomaterials.

[0060] (5) Take 10 mg of the FeS-5% Ti nanopowder prepared in (4) and evenly disperse it in a mixture of 475 μl of oxygen-free water, 475 μl of oxygen-free ethanol and 50 μl of Nafion resin to prepare an electrocatalytic material. Then, take 20 μl and apply it on a 1 cm×1 cm carbon cloth. After natural air drying under anaerobic conditions, the electrochemical catalytic reduction of N2 to NH3 is tested.

[0061] Comparative Example 1

[0062] (1) Add 4.2 g of ferric citrate and 0.93 mL of lactic acid to an anaerobic bottle containing 250 mL of LB medium, heat at 90°C for 20 min, and after the ferric citrate is completely dissolved, add 2.45 g of sodium thiosulfate and 2.1 g of Bio-Tris, and use sodium hydroxide to adjust the solution pH to 8.0;

[0063] (2) After passing argon for 20 min, sterilize at 121°C, 101 K Pa for 20 min. After sterilization, wait for the culture medium to cool, shake well, and inoculate Shewanella CN32 with an inoculum size of 5 × 10 8 The anaerobic bottle was placed in a shaker and cultured at 30°C and 180 r / min for 7 days.

[0064] (3) The black precipitate in the bottle was collected by centrifugation under anaerobic conditions, washed at least three times with oxygen-free water, and freeze-dried at -80°C for 30 h to obtain FeS nanomaterials.

[0065] (4) Take 10 mg of the FeS nanopowder prepared in (3) and evenly disperse it in a mixture of 475 μl of oxygen-free water, 475 μl of oxygen-free ethanol and 50 μl of Nafion resin to prepare an electrocatalytic material. Then, take 20 μl and apply it on a 1 cm × 1 cm carbon cloth. After natural air drying under anaerobic conditions, the electrochemical catalytic reduction of N2 to NH3 is tested.

[0066] Comparative Example 2

[0067] (1) 0.15 L 1.1 M Na2S was added to 0.25 L 0.57 M FeCl2, and the mixture was placed in an anaerobic chamber and reacted at room temperature for 3 days to obtain black particles. The precipitate was collected by centrifuge and centrifuged at 3000 r / min for 10 min, and then the precipitate was washed with deoxygenated water for at least 3 times and vacuum freeze-dried for 20 h to obtain chemically synthesized black FeS nanopowder.

[0068] (2) Take 10 mg of the FeS nanopowder prepared in (1) and evenly disperse it in a mixture of 475 μl of oxygen-free water, 475 μl of oxygen-free ethanol and 50 μl of Nafion resin to prepare an electrocatalytic material. Then, take 20 μl and apply it on a 1 cm × 1 cm carbon cloth. After natural air drying under anaerobic conditions, the electrochemical catalytic reduction of N2 to NH3 was tested.

[0069] Comparative Example 3

[0070] (1) 0.15L 1.1M Na2S was added to 0.25L 0.57M FeCl2, and titanium trichloride aqueous solution (Ti / Fe=1%, wt) was added. After shaking, the mixture was reacted in an anaerobic chamber at room temperature for 3 days to obtain black particles. The precipitate was collected using a centrifuge, centrifuged at 3000r / min for 10min, and then washed with deoxygenated water for at least 3 times, and vacuum freeze-dried for 20h to obtain chemically synthesized black FeS-1% Ti nanopowder.

[0071] (2) Take 10 mg of the FeS-1% Ti nanopowder prepared in (1) and evenly disperse it in a mixture of 475 μl of oxygen-free water, 475 μl of oxygen-free ethanol and 50 μl of Nafion resin to prepare an electrocatalytic material. Then, take 20 μl and apply it on a 1 cm×1 cm carbon cloth. After natural air drying under anaerobic conditions, the electrochemical catalytic reduction of N2 to NH3 is tested.

[0072] like Figure 2 As shown, it is the XRD spectrum of FeS-x%Ti prepared in each embodiment of the present invention and FeS prepared in Comparative Example 1. It can be seen that the main peak positions of biosynthesized FeS-x%Ti and FeS are the same, indicating that the doping has little effect on the crystal structure of the material.

[0073] like Figure 3 Shown are scanning electron microscope images of FeS-1% Ti prepared in Example 2 of the present invention and FeS nanopowder prepared in Comparative Example 1. From the SEM and related EDS images, it can be seen that the FeS nanomaterial synthesized based on biological method is loaded on the cell surface.

[0074] like Figure 4 As shown, the linear voltammetric curves (LSV) of FeS-1% Ti prepared in Example 2 and Comparative Example 3 of the present invention and FeS nanopowder prepared in Comparative Examples 1 and 2 are shown. It can be seen that compared with the comparative examples, the FeS nanopowders doped with different proportions of Ti 3+ Both can promote the reaction between nanomaterials and N2, and the Ti loaded on the cells 3+ The catalytic performance of doped FeS nanomaterials is better than that of undoped FeS and chemically synthesized FeS. 3+ The FeS nanomaterial has the best performance.

[0075] like Figure 5 As shown, it is the XPS full spectrum and fine map of FeS-1% Ti prepared in Example 2 of the present invention and FeS nanopowder prepared in Comparative Example 1. From the XPS results, it can be seen that the Ti element is successfully doped in FeS, and the Ti 3+ exists in the form of.

[0076] like Figure 6 As shown, it is a graph of the electrocatalytic nitrogen reduction performance of FeS-1% Ti prepared in Example 2 of the present invention. It can be seen intuitively that the prepared FeS-1% Ti nanomaterial has excellent electrocatalytic nitrogen reduction performance.

[0077] Figure 7 The results of multiple cycles show that after 5 repetitions, there is no significant change in the ammonia yield and Faraday efficiency, indicating that the new catalyst prepared by the present invention has good electrochemical durability, good cyclability, high sustainability, and can continuously produce ammonia.

[0078] The above description is only an embodiment of the present invention and cannot limit the patent protection scope of the present invention. Any equivalent structure or equivalent process transformation using the contents of the present invention specification, or direct or indirect application in the relevant technical field, which does not deviate from the basic characteristics of the present invention, is included in the patent protection scope of the present invention.

Claims

1. A Ti loaded on microbial cells 3+ The method for preparing doped makino ore material is characterized in that: The following steps are involved: (1) Add ferric citrate and lactic acid to an anaerobic bottle containing culture medium, heat it, add a soluble sulfur source and Bio-Tris, and adjust the solution pH to 7.0-9.0; The soluble sulfur source includes: at least one of sodium thiosulfate and sulfite; (2) Pass protective gas, sterilize, cool, inoculate Shewanella, and culture on a shaking table; (3) After the shaking culture, the culture medium solution turns pure black. Under anaerobic conditions, a titanium source is added to the culture medium and the pH is adjusted to 7.0-8.5, and the culture is continued in the shaking culture medium; (4) collecting the black precipitate by solid-liquid separation under anaerobic conditions, washing it with oxygen-free water, and freeze-drying it to obtain the product; The Shewanella is Shewanella putrefaciens ( Shewanela putrefaciens ) CN32; Step (1) specifically: the mass ratio of ferric citrate: lactic acid = (3.5-4): 1, the mass ratio of ferric citrate: sodium thiosulfate = (1-2): 1, the mass ratio of ferric citrate: Bio-Tris = (1.5-2.5): 1; the solid-liquid ratio of ferric citrate to culture medium: (4-5) g: 250 mL; Step (3) specifically: after culturing on a shaking table for 10-24 hours, the culture medium solution turns pure black. At this time, in an anaerobic chamber, titanium trichloride aqueous solution is added to the culture medium, and sodium hydroxide or ammonia water is used to adjust the pH to 7.0-8.5, and the culture medium is placed in a shaking table and continues to be cultured for 6-10 days; The mass ratio used in step (3) is Ti / Fe = 0.5% ~ 5%.

2. The method according to claim 1, characterized in that Step (1) is as follows: Add ferric citrate and lactic acid to an anaerobic bottle containing LB medium, heat at 90-100°C, add sodium thiosulfate and Bio-Tris after the ferric citrate is completely dissolved, and adjust the pH of the solution to 7.0-9.0 using sodium hydroxide or ammonia water.

3. The method according to claim 1, characterized in that Step (2) is as follows: after passing argon for at least 20 min, sterilize at 121°C, 101 K Pa for 20 min; after sterilization, wait for the culture medium to cool, shake well, and inoculate Shewanella with an inoculum size of 10 6 -10 10 / ml; put the anaerobic bottle in a shaker and culture it at 28-32 ℃ and 150-200 r / min.

4. The method according to claim 1, characterized in that: Step (4) is as follows: the black precipitate in the bottle is collected by centrifugation under anaerobic conditions, washed at least three times with oxygen-free water, and freeze-dried at -80°C for 10-30 h to obtain the product.

5. A Ti loaded on microbial cells prepared by the method according to any one of claims 1 to 4 3+ Doped with makinoite material.

6. A Ti loaded on a cell membrane prepared by the method according to any one of claims 1 to 4 3+ The application of doped makino ore nanomaterials is characterized by: As an electrocatalytic electrode material for electrochemical reduction of nitrogen.

Citation Information

Patent Citations

  • Preparation method of nano-metal sulfide

    CN102181495A

  • Biological nano hybrid system modified electrode as well as preparation method and application thereof

    CN114455692A